Double Stranded RNA in Human Seminal Plasma - Zagoskin, Maxim V.; Davis, Richard E.; Mukha, Dmitry V. (Frontiers in Genetics, 2017)
Recently, human semen was shown to contain cell-free nucleic acids, such as DNA, long single stranded RNA, and small RNAs – miRNA and piRNA. The RNAs have been suggested to have potential biological roles as communication molecules between cells and in the temporal and spatial regulation of gene expression in the male reproductive system. Here we demonstrate that human seminal plasma contains a variety of cell-free dsRNAs, describe a robust method to isolate this type of nucleic acid in preparative amounts, and discuss the potential biological roles of these molecules in inheritance. dsRNA plays a role in a variety of biological processes, including gene regulation, is extremely stable and can gain access to cells from the extracellular medium. We suggest that one of the possible functions of dsRNA in human seminal plasma may be to influence human oocytes and therefore, influence the offspring. It also remains possible that these dsRNAs might have potential use as biomarkers for the study of human physiopathological conditions and genetic variation.